(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the system of motion verbs in Russian and Uzbek from a comparative linguistic perspective.Special attention is given to typological differences that cause persistent learning difficulties among students.Russian motion verbs are characterized by aspectual opposition, prefixation, and directionality.Uzbek motion verbs, by contrast, rely more on analytical constructions and contextual indicators.The study identifies interference errors arising from learners’ native language transfer.Particular focus is placed on unidirectional and multidirectional verb pairs in Russian.The absence of direct structural equivalents in Uzbek complicates semantic interpretation.The research is grounded in functional, cognitive, and contrastive linguistics methodologies.Examples from educational practice illustrate common mistakes made by Uzbek-speaking learners.The findings highlight the role of linguistic worldview in mastering motion semantics.Pedagogical strategies for improving instruction are proposed.